NOVEL SURGA YANG DIRINDUKAN KARYA ASMA NADIA DALAM PERSPEKTIF PENDIDIKAN ETIKA ISLAM - Atika Zuhrotus Sufiyana; Maritha Anastasya Qomaria; Moh. Murtadho (VICRATINA, 2020)
Islam conveys knowledge to humans as a way of life for humans throughout the world. Humans are the perfect creation of Allah SWT with excellence from various fields, both spiritual or physical. Education is interpreted like mental, moral and physical guidance that is able to create high civilized human beings, then education is useful to improve personality by fostering a sense of educational responsibility. Islam that has lived and provided various types of characters With different names, humans must obtain an education that can have a function in settlement and peace as desired. for humans to realize harmony and equilibrium, knowledge that does not break from religion is like a perfect norm in the soul it self.